Penatalaksanaan Fisioterapi Pada Gangguan Fungsional Wrist Dan Hand Akibat Carpal Tunnel Syndrome Dengan Teknik Tendon Gliding Exercise Dan Self Neural Mobilization - Meida Hayati Meida Hayati; Arfian Hamzah; Yulisha Eva Oktaviani (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
The increasing prevalence of CTS cases from every year, especially in Banjarmasin, has led the authors to be interested in conducting research on "Management of Physiotherapy in Functional Disorders of the Wrist and Hand due to Carpal Tunnel Syndrome with the administration of Tendon Gliding Exercise and Self Neural Mobilization techniques". The purpose of the authors conducted this study is to determine the management of physiotherapy in functional wrist and hand disorders due to CTS. This research method uses 1 sample obtained directly with the examination results experiencing functional impairment of wrist and hand due to CTS. Retrieval of research data using a measuring instrument in the form of a Boston Carpal Tunnel Syndrome Quesionnare (BCTQ) questionnaire which will be taken at the time before and after the administration of interventions to determine the functional development of patients with CTS. Provision of intervention carried out for 4 weeks with a frequency of 5 meetings a week. Provision of tendon gliding exercise techniques with a dose of 5-10x reps and self-neural mobilization is given at a dose of 3 sets with 10x reps. The results of the study found an increase in functional wrist and hand as measured by BCTQ after given Tendon Gliding Exercise and Self Neural Mobilization interventions